Children's internal migration and subjective wellbeing of older parents left behind: Spiritual or financial support? - Lu, Ying; Lin, Yi-Yang; Qu, Jun-Qiao; Zeng, Yi; Wu, Wan-Zong (Frontiers in Public Health, 2023)
Against the background of population aging and large-scale internal migration, this study uses an ordered logit with two-way fixed effects to examine the effect of children’s internal migration on the subjective well-being of parents left behind. The study is based on the China Family Panel Studies database. The results show that children’s internal migration has a significant negative effect on the subjective well-being of parents left behind, mainly through the reduction of intergenerational spiritual support. Furthermore, intergenerational financial support significantly mitigates this negative effect. There is heterogeneity in the direction of the total well-being effect across parents’ preferences, as well as in the masking effect of financial support. However, the effect of financial support never fully offsets the effect of spiritual support. It is recommended that positive interventions be introduced to reduce the dependence of parents left behind on their children's spiritual support and to increase financial support for elderly parents left behind.